Recent advances in organocatalytic asymmetric aza-Michael reactions of amines and amides - Sharma, Pratibha; Gupta, Raakhi; Bansal, Raj Kumar (Beilstein Journal of Organic Chemistry, 2021)
Nitrogen-containing scaffolds are ubiquitous in nature and constitute an important class of building blocks in organic synthesis. The asymmetric aza-Michael reaction (aza-MR) alone or in tandem with other organic reaction(s) is an important synthetic tool to form new C–N bond(s) leading to developing new libraries of diverse types of bioactive nitrogen compounds. The synthesis and application of a variety of organocatalysts for accomplishing highly useful organic syntheses without causing environmental pollution in compliance with ‘Green Chemistry” has been a landmark development in the recent past. Application of many of these organocatalysts has been extended to asymmetric aza-MR during the last two decades. The present article overviews the literature published during the last 10 years concerning the asymmetric aza-MR of amines and amides catalysed by organocatalysts. Both types of the organocatalysts, i.e., those acting through non-covalent interactions and those working through covalent bond formation have been applied for the asymmetric aza-MR. Thus, the review includes the examples wherein cinchona alkaloids, squaramides, chiral amines, phase-transfer catalysts and chiral bifunctional thioureas have been used, which activate the substrates through hydrogen bond formation. Most of these reactions are accompanied by high yields and enantiomeric excesses. On the other hand, N-heterocyclic carbenes and chiral pyrrolidine derivatives acting through covalent bond formation such as the iminium ions with the substrates have also been included. Wherever possible, a comparison has been made between the efficacies of various organocatalysts in asymmetric aza-MR.
Keywords: asymmetric aza-Michael reaction; covalent bonding catalysis; nitrogen heterocycles; non-covalent bonding catalysis; organocatalysis